Juventude rural na Região Celeiro do Rio Grande do Sul: motivos para ficar, razões para voltar - Souza, Isabel Vanessa Robaert de (2023)
This research began empirically about 10 years ago, through professional work in technical assistance and rural extension, at Emater/RS – Ascar do Rio Grande do Sul, and continues to be instigating in its path of unveiling, as a research topic, the reasons for return and permanence of rural young people to the countryside, in the Celeiro region of the state, even following the path contrary to statistics, which point to around 85% of urbanization in Brazil. Following this justification, young people leave the countryside for various reasons, including lack of income, autonomy, participation in rural property management, problems in family relationships, and young women are the ones who leave the countryside the most. As objectives of the work, the research points to similar hypotheses for their return and permanence, with identification with the activity and the rural environment being the main reason given by young people for this. Their return and permanence, as well as their income or remuneration, are evident in all interviews and observations as well, the family bond and the rural way of life as the reasons given by young people. The research method used was exploratory qualitative research, through participant action research. Bibliographical reviews were carried out on the themes of Rural Youth, in the areas of human, agrarian and social sciences, in view of the scope of the theme, as well as the territory, region, rural development and public policies as contributors to the process of permanence of the youth in the field. In all themes, the contributions of geographers with the proposed questions were researched. For field work, the Entrepreneurship and Development Course for Rural Youth, carried out by the Training Center for Farmers of Bom Progresso, from Emater/RS – Ascar from the intermediate region of Ijuí, was the research laboratory, where 24 young people participated, from 10 municipalities. We sought to demonstrate the perspective of young people, the main subjects in focus, building analyzes and reflection results.